Changing values: a view of Turkey and Egypt - Thorpe, Michael; Jayashree, P.; Hosie, P. (Kaizen Publishing, 2011)
Economic development is considered to bring with it pervasive social and cultural changes. In today’s global economy, greater economic security is being accompanied by changes in the nature of work and in the levels and styles of social interaction. Evidence from developed economies suggest that there has been a resulting shift within societies towards so-called post-materialist values, with greater priority afforded by individuals to self expression and quality of life issues. While such shifts have been observed over time, across generations, differences in values have also been evident between older and younger cohorts within populations. It is the ageing of these younger cohorts which is considered to drive inter-generational shifts in values. Currently in many developing economies, including parts of the Middle East and North Africa (MENA) region, it appears that significant cultural changes may be occurring, manifest in a various ways. Using data from recent waves of the World Values Survey, this paper analyses the nature of cultural differences within Egypt and a neighbouring Eurasian state, in line with established hypotheses from the literature.